Why not fully spend a conditional block grant? - Riemer P. Faber; Pierre Koning (Institute for the Study of Labor (IZA), 2012)
This paper studies a conditional block grant that Dutch municipalities receive for welfare-to-work programs. Many municipalities do not fully use this grant, although programs are beneficial for them. We argue that municipalities incur expenses to use the grant. If these costs are substantial, then it is optimal not to fully use the grant. Based on municipality-specific data on grants and actual expenditures, we estimate that municipalities have to add about 90 cents from their own resources to spend 1 euro of the grant. As a result, the conditional block grant is de facto a closed-ended matching grant.
Keywords: H77; H20; H71; I38; 330; intergovernmental grants; conditional block grants; welfare-to-work programs; Kommunaler Finanzausgleich; Aktivierende Sozialhilfe; Kommunale Ausgaben; Niederlande